Durvalumab following definitive chemoradiotherapy among patients with stage III NSCLC in the Thai population: a real-world, multicenter observational study - Sitthideatphaiboon, Piyada; Reungwetwattana, Thanyanan; Jaruhathai, Sureerat; Supavavej, Archara; Limpawittayakul, Piyarat; Maneenil, Kunlatida; Korphaisarn, Krittiya; Suksombooncharoen, Thatthan; Thongthieang, Luangyot; Sathitruangsak, Chirawadee; Chayangsu, Chawalit; Ratanabunjerdkul, Hataiwan; et al. (Frontiers in Oncology, 2025)
BackgroundIn locally advanced non-small cell lung cancer (LA-NSCLC), durvalumab as consolidation therapy following definitive chemoradiotherapy (CRT) was established as the standard of care. Given the heterogeneity of patients with LA-NSCLC, the present study evaluated the efficacy and safety of durvalumab in a real-world, multicenter observational study.MethodsPatients with LA-NSCLC, whose disease had not progressed following CRT and receiving ≥1 dose of durvalumab as part of the expanded access program (EAP) in Thailand and outside EAP, were included. In addition to descriptive statistics, survival probability was determined using the Kaplan–Meier method.ResultsA total of 82 patients from 12 centers in Thailand were enrolled. The median age was 63 years, 74% were men, 72% had non-squamous NSCLC, and 20% of patients had an epidermal growth factor receptor (EGFR) mutation. Only 13.4% of patients were tested for programmed death-ligand 1 (PD-L1), and 54.5% had PD-L1 expression. Most patients (84%) received concurrent CRT, and carboplatin/paclitaxel was the most commonly used. Of the patients, 89% received radiotherapy (RT) dose ≥60 Gy with a median time of durvalumab initiation from the end of RT being 42 days. Overall, 57% of patients completed the 12-month treatment with a median of 24 cycles. Objective response rate (ORR) and disease control rate (DCR) were 41.3% and 86.7%, respectively. With a median follow-up time of 43.3 months, 2-year progression-free survival (PFS) and 2-year time to second objective disease progression (PFS2) were 63.1% and 81.6%, respectively. Immune-related adverse events (irAEs) of any grade and grade ≥ 3 were 25.6% and 9.8%, respectively. Pneumonitis was the most frequent irAE (17%), and 6% were grade ≥ 3, leading to discontinuation in six patients (7.3%).ConclusionsDurvalumab following definitive CRT demonstrated promising outcomes and was well-tolerated in this real-world study. These findings support the utilization of durvalumab for enhancing outcomes in patients with unresectable LA-NSCLC within Asian populations.